Análisis del sistema eléctrico para disminuir pérdidas de energía en la empresa Pulpa Moldeada s. a - Gallo Pérez, Wilmer Fernando (2022)
Electrical power systems are exposed to different types of disturbances, whether internally or externally, which are manifested in deviations from the adequate conditions of voltages, currents or frequencies, which generates poor power quality for the end user, for which This research project contemplates an analysis of the electrical system in the Pulpa Moldeada S.A factory to reduce electrical energy losses, by measuring the parameters stipulated by the Agency for the Regulation and Control of Energy and Non-Renewable Natural Resources 002/20 with the purpose of verifying compliance with the quality indices, with the collection of information on the data of the motor plates, transformers, capacitor bank, grounding, conductor sizes, protection equipment, and taking into account Consider that the factory works 24 hours a day on different working days, a simulation is carried out in the Et software. ap, in order to compare the data obtained with the fluke 435 load analyzer and the software, once the comparison is made, the simulations are carried out, giving solutions to the problems of current harmonics and for the mitigation of Flicker , Sags and Swell that are present in the factory due to the high power motors that cause these effects, the technical and economic analysis is focused on mitigating the aforementioned disturbances with the application of filters and the implementation of frequency inverters for the loads of greater power which will lower the billing cost of the factory increasing energy efficiency.